1885, Laws of the University of Vermont State Agricultural College, ch. 6, §§ 4 & 9 (The Free Press Association). - (:unkn) unknown (General Publisher, 1885)
Sec. 4: Rooms shall be held by students subject to the condition that all rules, for securing quiet, order, and cleanliness in the rooms, halls, and premises, are strictly observed. Any violation of these rules, either by themselves or visitors, shall subject the occupants to forfeiture of their right to the room. Self-boarding in any of the rooms; the keeping of a dog or cat; cutting or splitting wood in the rooms or halls; shouting, or throwing anything, from the windows; pasting pictures on or otherwise injuring the walls; loud and boisterous noises in the rooms or halls; playing on musical instruments during recitation hours or after ten o'clock at night; gatherings of students in the rooms after the same hour; the keeping of fire-arms or gunpowder except under direction of the Military Instructor; bringing into the rooms any fermented or distilled liquors; are prohibited. Sec. 9. No student shall use gun powder or fire-arms in the buildings, or on the adjacent grounds of the University, except under direction of the Military Instructor. No smoking shall be allowed in any of the halls or public rooms of the University; nor shall any intoxicating drinks be brought upon the University premises.”
--
Keywords: POSSESSION